Master clinical medical knowledge at certificated-doctor-level with deep learning model - Ji Wu (Nature Portfolio, 2018)
AI is used increasingly in medical diagnostics. Here, the authors present a deep learning model that masters medical knowledge, demonstrated by it having passed the written test of the 2017 National Medical Licensing Examination in China, and can provide help with clinical diagnosis based on electronic health care records.